KONSTRUKSI MAKNA JENANG SENGKOLO SEBAGAI MEDIA KOMUNIKASI SIMBOLIK DALAM RITUAL MALAM SURO DI DESA UTERAN, KABUPATEN MADIUN - Rakhma Widya Dharojah; Malik Ibrahim; Kinanti Kartikasari; Raisa Sabilla; Anggraini Lestari (Nusantara Hasana Journal, 2025)
This study explores the construction of meaning of jenang sengkolo as a medium of symbolic communication in the Malam Suro ritual in Uteran Village, Madiun Regency. The tradition of jenang sengkolo is not merely a culinary practice, but a cultural symbol that conveys prayers, hopes, and resistance to misfortune. Employing a qualitative approach with ethnographic methods, data were collected through in-depth interviews, participant observation, and triangulation with key informants including community elders, cultural figures, and ritual participants. The findings reveal that jenang sengkolo, with its two main colors white and abang (red) symbolizes purification, gratitude, protection from calamities, and closeness to God. Within the framework of symbolic interactionism, the meanings of jenang sengkolo are constructed through social interaction and negotiation across generations, with elders emphasizing its philosophical-spiritual aspects while younger generations tend to view it as cultural identity or tradition. The study concludes that jenang sengkolo functions as a living symbolic medium that strengthens collective identity, social cohesion, and the continuity of Javanese cultural values. Academically, this research enriches cultural communication studies, while practically it provides deeper understanding for younger generations to preserve this tradition as both local wisdom and cultural identity.